Literature Review : Kebebasan dan Tanggung Jawab dalam Media : Tantangan di Dunia Digital - Wardanu, Aditya Putra; Tri Amukti, Fajar Dio Wahyu; Winarno, Agung (Journal of Management and Bussines (JOMB), 2025)
This study aims to explore the relationship between freedom and responsibility in social, political, and legal contexts. The main focus of the study is how individual freedom can be implemented in a balanced manner with social responsibility to create harmony in society. The method used is a systematic literature review by filtering relevant research articles in the period 2014–2024. Of the 50 articles identified, 20 articles were selected based on relevance, content quality, and publishing sources. The results of the study indicate that freedom without responsibility can lead to social conflict, abuse of freedom, and societal instability. In the context of media, freedom of expression in the digital era brings benefits in the form of wider access to information, but also poses challenges such as the spread of false information and hate speech. Therefore, digital media regulation is needed to maintain a balance between individual rights and public interests. In addition, effective public policies must consider social responsibility to prevent abuse of freedom in various aspects, including freedom of religion, freedom of the press, and freedom of expression in education. The conclusion of this study emphasizes that freedom must be accompanied by responsibility in order to provide maximum benefits to society at large. Wise regulation, code of ethics, and legal oversight are important factors in balancing both concepts to create a stable, harmonious, and sustainable social environment. Keywords: Keywords: Journalistic Ethics, Individual Freedom, Public Policy, Media Regulation, Social Responsibility